The Conduct of War - Fuller, J. F. C.; Translated by Khan, Ghulam Jeelani, Lt. Col. (Lahore Suhail Publications, 2007)
A study of the impact of the French, industrial, and Russian revolutions on war and its conduct.
Include Maps.
It is translated in Urdu by Lt. Col. Ghulam Jeelani Khan
Keywords: Military art and science -- Military history, Modern -- War and society -- Europe